Mitochondria organize the cellular proteostatic response and promote cellular senescence - Yanjun Li; Lei Liu; Yushan Zhu; Quan Chen (Cell Stress, 2019)
Mitochondria have relatively independent protein quality control systems, including their own chaperones for protein folding and AAA proteases for protein degradation. Accumulating evidence has shown that cytosolic proteins and disease-causing misfolded proteins can be translocated into mitochondria and then impinge upon their function. It is important to understand the interplay between cellular proteostasis and mitochondria, as impaired proteostasis and mitochondrial dysfunction are causally linked with aging and age-related disorders. This review highlights our recent finding showing that the outer mitochondrial membrane protein FUNDC1, a previously reported mitophagy receptor, interacts with the chaperone protein HSC70 to mediate the mitochondrial translocation of cytosolic proteasomal substrates via the TOM/TIM complex into the mitochondrial matrix where they can be degraded by LONP1 protease. Excessive accumulation of unfolded proteins within mitochondria triggers the formation of Mitochondrion-Associated Protein Aggregates (MAPAs), which are subsequently autophagically degraded in a FUNDC1-dependent manner. We suggest that mitochondria actively organize the cellular proteostatic response and that the interaction between FUNDC1 and HSC70 may represent a new link between impaired proteostasis, mitochondrial dysfunction and cellular aging.